Misconception and Legal Problems of Authority to Perform Medical Actions in Nursing Administrative Law - P. Sibuea, Hotma; Seno Wijanarko, Dwi; Johardi Wirogioto, Ali; Lorenly Nainggolan, Indra; Siagian, Katrina (Journal of World Science, 2023)
According to Article 29 paragraph (1) of Law Number 38 of 2014, nurses have several duties, namely as providers of nursing care, counselors and client counselors, managers of nursing services, nursing researchers, and task performers based on delegated authority and/or tasks in specific limited circumstances. One of the nurse's tasks that receives focused attention is "as a task performer based on delegated authority." According to Article 32 paragraph (2) of Law Number 38 of 2014, the implementation of nurse tasks based on delegated authority regulated in Article 29 paragraph (1) letter e of Law Number 38 of 2014 is carried out by nurses in a "delegative and mandate" manner. The aim of this research is to identify and analyze misconceptions and legal problems in performing medical actions in nursing administrative law. The research method used is a normative juridical research method. The research results are as follows: First, the term "delegated authority" is not accurately used in the context of nurse task implementation for performing medical actions. Second, the more appropriate term is "cooperation." Suggestions that can be put forward are as follows: First, Law Number 38 of 2014 concerning Nursing needs to be amended. Second, the term "delegated authority" in the legal relationship between medical personnel and nurses regulated in Article 29 paragraph (1) letter 3 of Law Number 38 of 2014 needs to be changed and replaced with the term "cooperation.